Comparison of different treatment modalities of tocilizumab in children with systemic juvenile idiopathic arthritis - M. M. Kostik; M. F. Dubko; L. S. Snegireva; V. V. Masalova; T. L. Kornishina; T. S. Likhacheva; I. A. Chikova; E. A. Isupova; E. M. Kuchinskaya; N. I. Glebova; O. V. Kalashnikova; V. G. Chasnykh (Вопросы современной педиатрии)
Aim: to perform retrospective evaluation of tocilizumab (TCZ) treatment every 2 and 4 weeks. Patients and methods: 33 children with systemic juvenile idiopathic arthritis (sJIA) were observed. Results: children, who need TCZ treatment every 2 weeks had more severe sJIA course. Patients which were treated every 4 weeks had higher TCZ efficacy, no new cases of macrophage activation syndrome (MAS), lower frequency of organ involvement and relapses during TCZ treatment. In 5 (20,8%) children of this group the TCZ-free remission was achieved, and in 3/5 children total drug-free remission lasted the maximum 1085 days was reached. Only 1 children in 4 weeks group developed relapse which leaded to re-start of TCZ treatment with the same efficacy as at first. No patients, who were treated every 2 weeks experienced TCZ-free remission. Also 4 cases of MAS were detected in children who had MAS before the start of TCZ. In 3/4 TCZ was discontinued but in 1 MAS TCZ accompanied with corticosteroids was prolonged. No new MAS cases were detected during this study. Infusion reactions lead to TCZ discontinuation were in 9,1%. 1 death (3,0%) during the trial. Conclusions: we offered the set of clinical and laboratorial criteria of high and low risk patients who need TCZ treatment every 2 and 4 weeks consequently.Key words: systemic juvenile idiopathic arthritis, interleukine-6, tocilizumab.